Tinjauan Kekuatan Dan Biaya Struktur Atap Baja Ringan Dan Baja Konvensional Gedung Diklat Rsup Dr. Kariadi Semarang - Wahab, Muhammad, Ir. H. Suhendro Trinugroho M.T (2017)
This final project aims to study the safety of the roof structure of the light steel material installed on workshop building roof of RSUP Dr. Kariadi Semarang. Then it is compared to the one that uses the roof structure of the conventional steel material. The trend in the construction, especially the recent construction roof, tends to the use of the light steel material. From the research, it was obtained: the calculation of re-control of the roof structure of RSUP. Dr. Kariadi Semarang which used the structure of the light steel roof frame of type 1 are 2 unsecured bars, they are: bar number 22 which length is 1949 mm, and the pressure force is 10081,3 N and the bar number 30 which length is 1949mm and the pressure force is 10169,2 N. Both of the bars are unsecured on the lateral torsial buckling. As the comparison, if using the roof the structure of the conventional steel with a distance of among easels is 1.2 m, it was known that the profile used is 2L 15x15x4, 2L 25x25x3, 2L 30x30x4, 2L 35x35x6, with a total weight of 8295,718 kg. Therefore, the cost that must be spent is as much as IDR136,000,000 which is more expensive than the cost the roof structure that uses the material of the light steel that is as much as IDR80,500,000. For the re-design of the roof structure of RSUP. Dr. Kariadi Semarang which uses the most efficient and secured roof frame structure of the conventional steel, it was obtained by using the effective distance of among easels that is 4.67 m with the size of profile is 2L 20x20x3, 2L 25x25x4, 2L 30x30x4, 2L 35x35x6 and the size of gording is C100x50x20x4. The cost that must be spent is IDR105,550,000 which is more expensive than the cost the roof structure that uses the material of the light steel that is as much as IDR 80,500,000.